2018
DOI: 10.1093/biolre/ioy202
|View full text |Cite
|
Sign up to set email alerts
|

Sperm capacitation is associated with phosphorylation of the testis-specific radial spoke protein Rsph6a†

Abstract: Mammalian sperm undergo a series of biochemical and physiological changes collectively known as capacitation in order to acquire the ability to fertilize. Although the increase in phosphorylation associated with mouse sperm capacitation is well established, the identity of the proteins involved in this signaling cascade remain largely unknown. Tandem mass spectrometry (MS/MS) has been used to identify the exact sites of phosphorylation and to compare the relative extent of phosphorylation at these sites. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 58 publications
(75 reference statements)
1
15
0
Order By: Relevance
“…Currently, there are no human studies in the literature. This protein is important for normal ciliary and flagellar function (Abbasi et al, ; Eriksson, Ansved, Anvret, & Carey, ; Paudel et al, ). In humans, the expression of RSPH6A is testis‐specific, and the protein localizes in particular in the sperm flagella.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are no human studies in the literature. This protein is important for normal ciliary and flagellar function (Abbasi et al, ; Eriksson, Ansved, Anvret, & Carey, ; Paudel et al, ). In humans, the expression of RSPH6A is testis‐specific, and the protein localizes in particular in the sperm flagella.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that RSPH6A is specifically expressed in human testes and that the knockout (KO) male mice are infertile due to short, immotile SPZ. However, currently little is known about the role played by RSPH6A protein in the mammalian flagellar axoneme and its implication in male fertility (Abbasi et al, ; Paudel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Super-resolution imaging with stochastic optical reconstruction microscopy suggests that the catalytic PKA subunit can be localized in the sperm axoneme [ 7 ]. RSPH6A localized in the axoneme was identified as a PKA substrate candidate using phospho-proteomic analysis [ 2 ]; however, this study reveals that S17 and S20 of RSPH6A are not essential for male fertility. As is the case for RSPH6A [ 4 ], disruption of axonemal proteins often leads to impaired flagellar formation [ 8 ], which makes it challenging to analyze their function in mature spermatozoa using a straight KO approach.…”
mentioning
confidence: 98%
“…Although it is well known that phosphorylation events that start with protein kinase A (PKA) are essential for capacitation [ 1 ], downstream phosphorylated molecules and their functions are not well understood. Using phospho-proteomic and subsequent biochemical analyses, we previously identified phosphorylation residues (S17 and S20) of radial spoke head 6 homolog A (RSPH6A) that were associated with capacitation [ 2 ]. RSPH6A is an evolutionarily conserved and testis-enriched protein, and thought to be a component of the radial spokes in the flagellar axoneme [ 2–4 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation